Predicting the marital satisfaction based on marital burnout, loneliness and sexual function in married students - parisa dadoo; solmaz dabiri (مجله علوم روانشناختی, 2019)
Background: Marital satisfaction is one of the common concepts used for assessing happiness and stability in a marriage. It is a multidimensional concept that is affected by several  factors such as marital  burnout , loneliness and sexual  function. Aims:  The purpose of this study was   to predict marital satisfaction based on  marital burnout, loneliness and sexual function of married students. Method: The research method was correlation which is categorized as descriptive research methods. The statistical population included all married female students of  Karaj Islamic Azad University who were studying in the academic year 97-98. Of the 1400  married women students, 300 person selected by convenience sampling method. Data were collected by Enrich's marital satisfaction questionnaire (1989), Pines's marital burnout (1996), Dehshari's et al. loneliness (1387) and sexual function of women of Rosen's et al. (2000). Results: The results of statistical analysis showed that there was a significant negative correlation between marital burnout, loneliness and marital satisfaction, and a significant positive correlation between sexual function and marital satisfaction (p<0/01).  Also, variables  of  marital burnout, loneliness and  sexual function, 14% of the variance in  marital satisfaction of  women married students  was explained(p<0/01). Conclusion:  It can be concluded that the variables of  marital burnout, loneliness, and sexual function play an important role in the marital satisfaction of married female students.